Role of CT in Assessment of Unresectable Wilms' Tumor Response after Preoperative Chemotherapy in Pediatrics - Huda Refaie; Mohamed Sarhan; Ashraf Hafez (The Scientific World Journal)
The purpose of this study was to define the structural response of unresectable Wilms' tumor following preoperative chemotherapy by computed tomography (CT). We also compared CT changes in relation to histopathological nature. The study included 36 patients with 41 nephroblastomas. All were examined by CT before preoperative chemotherapy using multiphasic CT protocol study. The unresectability was diagnosed by CT imaging. All patients were subjected to fine-needle biopsy (FNB) to confirm the diagnosis and to define the histopathological type before preoperative chemotherapy. Five patients had unfavorable pathology and 31 patients with 36 nephroblastomas had favorable pathology. All patients received first line of treatment. Follow-up of these patients by CT at the 6th week was reviewed. All of our patients were diagnosed as unresectable Wilms' tumor by CT. Preoperative chemotherapy was started. Among our patients, 28 (77.8%) gave good response in the form of significant reduction in tumor size, disappearance of one tumor in two cases with bilateral WT and inferior vena cava (IVC) thrombus, and increased nonenhancing necrotizing content. Two patients with unfavorable pathology did not show any response. The remaining six patients gave partial response. CT can be used to evaluate tumor response and resectability after preoperative chemotherapy with high accuracy. The response to preoperative chemotherapy is not related to the histopathological classifications.